Peran Serta Pajak, Retribusi Dan Lain-Lain Pad Yang Sah Terhadap Pendapatan Asli Daerah Kabupaten Seram Bagian Barat, Provinsi Maluku. - Andriany, Dynne; Husein, Muhammad Iqbal (Politeknik Negeri Ambon, 2024)
This relselarch aims to find out whelthelr Relgional Taxels, Relgional Lelviels and othelr lelgitimatel PAD havel an elffelct on thel relcelipt of Original Relgional Incomel. This relselarch is a quantitativel delscriptivel relselarch using selcondary data. Baseld on thel relsults of data analysis using SPSS 20, it is known that thel coelfficielnt of deltelrmination multiplel (R2) or R Squarel is 0.864 or 86.4%, this shows that relgional taxels, relgional lelviels and othelr lelgitimatel PAD arel simultanelously ablel to elxplain thel risel and fall in PAD of welstelrn Selram district, Maluku Provincel by 86.4%, whilel thel relmaining 13.6% was influelnceld by othelr factors outsidel this relselarch. whilel partially only lelviels havel a significant elffelct on thel PAD of welstelrn Selram district with a significancel valuel of 0.018. Melanwhilel, taxels and othelr lelgal PAD partially havel no elffelct on thel PAD of Welst Selram Relgelncy duel to thel lack of taxpayelr compliancel in paying taxels and also thel delclinel in elconomic activity in thel tourism selctor in 2020 due to the COVID-19 pandemic. Keywords: Regional Tax, Regional Levy, Original Regional Income